A Combination of Low Doses of Fluvastatin and Valsartan Decreases Arterial Stiffness in Patients After Myocardial Infarction: A Pilot Study - Jurij Hanžel; Žiga Piletič, MD; Martina Turk, MD; Barbara Eržen, MD, PhD; Mišo Šabovič, MD, PhD (Elsevier, 2015)
Background: Despite optimum treatment, patients who experience myocardial infarction are still at high risk for future events. Objective: We evaluated the effect of 30 days of treatment with combination of low, subtherapeutic doses of fluvastatin and valsartan on arterial stiffness in patients after myocardial infarction, a therapy that has not been used yet. Methods: Fourteen male patients with a history of myocardial infarction were enrolled into a pilot double-blind randomized controlled study. They were allocated to receive 10 mg fluvastatin and 20 mg valsartan or placebo for 30 days in addition to their regular pharmacotherapy. Carotid-femoral pulse wave velocity was measured on inclusion, after 30 days, and after 3 months. Results: Mean (SD) carotid-femoral pulse wave velocity decreased significantly in the treatment group after 30 days and persisted at lower values after 3 months (from 8.4 [1.5] m/sec to 7.3 [1.1] m/sec to 7.2 [0.8] m/sec; P < 0.05). The 95% CI for decrease after 30 days in the treatment group was 0.5-1.6. Only nonsignificant changes were observed in the control group. Serum lipid levels and arterial blood pressure did not change significantly in any group. Conclusions: The treatment resulted in a significant and sustained improvement of arterial stiffness in male patients with a history of myocardial infarction, which highlights the need for further study of this new approach.